Determination of Economic Value using the EOQ and ROP Approaches in the Raw Material Control System - Arsyad Sumantika; Ganda Sirait; Elva Susanti; Elsya P. L. Tarigan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Inventory is one of the fundamental aspects of the company, not only the production process but also related departments need inventory. If the material inventory is too little, the production process is disrupted which in the end the delivery schedule is also disrupted, whereas if the material inventory is too much, the material storage costs incurred by the company will increase. The purpose of this research is to maximize material inventory and determine the right time for reordering raw materials. The methods used are EOQ, ROP, and ITO. Data collection was carried out quantitatively in food canning companies to determine economic orders. Based on the calculation results, the level of economical purchase of raw materials using the EOQ method approach is 54.64 kg per order and the recommended number of reorders is 45 kg per order with a safety stock level of 10.16 kg/day.